2017
DOI: 10.1016/j.nicl.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Structurofunctional resting-state networks correlate with motor function in chronic stroke

Abstract: PurposeMotor function and recovery after stroke likely rely directly on the residual anatomical connections in the brain and its resting-state functional connectivity. Both structural and functional properties of cortical networks after stroke are revealed using multimodal magnetic resonance imaging (MRI). Specifically, functional connectivity MRI (fcMRI) can extract functional networks of the brain at rest, while structural connectivity can be estimated from white matter fiber orientations measured with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
4
10
0
Order By: Relevance
“…Decreased connectivity of the alpha and beta bands in resting‐state paradigms has been reported using other EEG approaches (Dubovik et al., 2012, 2013; Wu et al., 2015). The decreased alpha (10–15 Hz) connectivity within a prefrontal‐cerebellar network in the stroke group is consistent with previous findings from our laboratory indicating decreased fMRI functional connectivity in a similar network after stroke (Kalinosky et al., 2017). The beta (15–20 Hz) band decreased connectivity consisted of prominent nodes in the lesioned hemisphere's sensory/parietal regions indicating it may be a marker of sensorimotor dysfunction that often occurs after stroke (Inman et al., 2012; Platz et al., 2000; Rossiter et al., 2014; Sharma et al., 2009; Wu et al., 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased connectivity of the alpha and beta bands in resting‐state paradigms has been reported using other EEG approaches (Dubovik et al., 2012, 2013; Wu et al., 2015). The decreased alpha (10–15 Hz) connectivity within a prefrontal‐cerebellar network in the stroke group is consistent with previous findings from our laboratory indicating decreased fMRI functional connectivity in a similar network after stroke (Kalinosky et al., 2017). The beta (15–20 Hz) band decreased connectivity consisted of prominent nodes in the lesioned hemisphere's sensory/parietal regions indicating it may be a marker of sensorimotor dysfunction that often occurs after stroke (Inman et al., 2012; Platz et al., 2000; Rossiter et al., 2014; Sharma et al., 2009; Wu et al., 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The motor cortex and cerebellum together have been shown to be involved in plasticity during motor training and in sensorimotor integration (62). Past imaging studies have shown that the connectivity between the cerebellum and parietofrontal areas are related to post-stroke motor function (63, 64).…”
Section: Discussionmentioning
confidence: 99%
“…Third, based on clear a priori hypotheses, we focused on defined prefrontal-premotor connections at the cortical level. The present results are not exhaustive, and the state of other motor networks, such as prefrontal-subcortical (45) or prefrontal-cerebellar circuits, might also influence comparable analyses.…”
Section: Discussionmentioning
confidence: 91%